Indonesian public officials after erroneous statements about COVID-19: An application of image restoration theory - Andarini, Rindang Senja; Pratiwi, Miftha; Setiyowati, Rini; Santoso, Anang Dwi (Frontiers in Political Science, 2023)
The image of the Indonesian public officilas whose reputations are the topic of this study will be examined in terms of the tactics and strategies they used to restore their reputations after making false claims and policies on COVID-19. The significance of this study can be separated into two categories. First, the application of image restoration theory to public organizations and public officials is uncommon. Second, it is essential to analyze the application of this theory in the diverse social, political, and economic contexts of emerging nations; as a result, these distinctions may lead to varied research conclusions. A dataset of 2,000 Instagram posts by Indonesian pulic officials was generated in order to conduct content analysis. This study reveals that public officials in Indonesia employ a variety of strategies and tactics to improve their public image. This study also found that reducing offensiveness, evading responsibility, and taking corrective action are the three most commonly seen practices among Indonesian public officials. This study confirms that denial and mortification are employed exceedingly infrequently in non-Western countries. This study has the practical implication that public officials or the public relations experts who represent them must be cautious since it can have severe implications on their image.